Performance of a novel dual-magnet tri-stable piezoelectric energy harvester subjected to random excitation. (1st July 2021) - Sun, Shuailing; Leng, Yonggang; Su, Xukun; Zhang, Yuyang; Chen, Xiaoyu; Xu, Junjie
Graphical abstract: Highlights: A novel dual-magnet tri-stable piezoelectric energy harvester is designed, modeled and tested. The harvester can achieve mono-, bi- and tri-stable states under different structural parameters. Nonlinear dynamics and energy harvesting performance of the harvester in the bi- and tri-stable states are investigated in a comparative way. The output performance of the harvester under random excitation depends on its potential well characteristics and excitation strength. Abstract: Usually conventional nonlinear tri-stable piezoelectric energy harvesters (TPEHs) contain two external magnets, which make both the system structure and dynamic analysis more complex. Herein, a novel dual-magnet TPEH with only one external magnet is proposed. This TPEH consists of a rectangular magnet, a piezoelectric cantilever beam, a ring magnet and a base. Next, the lumped-parameter model of the TPEH is established to obtain the dynamic equation, circuit equation, magnetic force expression and potential function. The analysis of the magnetic force expression and potential function finds that the system degenerates from a tri-stable state to a bi-stable state, and then to a mono-stable state with the increase of magnet distance due to the changes of magnetic force. Subsequently, Runge-Kutta method is used to simulate the nonlinear dynamics and energy harvesting performance of the energy harvester under the filtered Gaussian white noise over the frequency range of 0–120 Hz. Simulation results shows that the harvester changes from intra-well movement to inter-well movement with a few transitions, and then to inter-well movement with many transitions as excitation level increases. Additionally, the output performance in the bi-stable state is better than that in the tri-stable state when the excitation is small, and the output performance in the tri-stable state is better than that in the bi-stable state when the excitation is large enough. The reason is that the depth and width of the outer potential wells in the tri-stable state are deeper and narrower, while the distance between the two outer wells in the tri-stable state is larger, when compared to the bi-stable state. Finally, designed experiments are carried out to determine the parameters in the dynamic equation and measure the energy harvesting performance of the TPEH. Experimental results are consistent with simulation results. This study suggests that it is practicable to use the dual-magnet structure for constructing a multi-stable piezoelectric energy harvester.